A PHONO-PRAGMATIC ANALYSIS OF ASSERTIVENESS AND RHETORICAL QUESTIONING IN SELECTED ENGLISH AND ARABIC ELECTION SPEECHES - Gumar, Ahmed; Al-Zubaidi, Nassier (Al-Adab Journal, 2025)
The study presents a phono-pragmatic analysis of the argumentative strategies of assertiveness and rhetorical questioning in selected English and Arabic election speeches. Assertiveness is a strategy used to convey conviction and determination to the discourse. Rhetorical questioning is a strategy that is not used to elicit an answer, but to bring a problem to the minds of people and to make them think of it. To convey such meanings prosodically, politicians use a set of prosodic maxims with these strategies. The study aims at investigating the contribution of prosodic features and maxims to the transfer of the pragmatic meanings associated to these strategies. It also examines the universality of these argumentative strategies and their prosodic maxims. It is hypothesized that there is a correlation between the prosodic maxims and the argumentative strategies under investigation, and that they are universal in the English and Arabic election speeches. To test the validity of the study hypotheses, two TV shows are selected. They are the English TV show “Ohio U.S. Senate Debate”, which is broadcasted on the American NBC4 channel, and the Arabic one “The Opposite Direction”, which is broadcasted on Al-Jazeera Channel, are selected. To analyze the selected data, synthesis of Braga and Marques’ (2004) phono-pragmatic model and Wennerstrom’s (2001) discoursal functions of intonation model are adopted. The study comes up with the findings that there is a correlation between the prosodic maxims and argumentative strategies, that they are used universally, and that some variables of each prosodic maxim are more frequently used than others.